What Is the Relationship Between Body Mass Index, Sex Hormones, Leptin, and Irisin in Children and Adolescents? A Path Analysis - Zhang, Li; Peng, Xingwang; Wang, Yuanyuan; Cao, Ruiyao; Zhang, Zizhe; Fu, Lianguo (Frontiers in Pediatrics, 2022)
Objective: The present research aimed to study the relationship between body mass index, sex hormones, leptin and irisin in children and adolescents with different body types. Methods: In this study, a stratified cluster random sampling method was used to select students aged 8-15 years within two nine-year schools as the research subjects. Based on a case-control study, 183 overweight/obese students were selected. After using sex and age matching to create a matched sample of normal weight students, a total of 366 students, including 214 boys (58.5%) and 152 girls (41.5%) were included. We measured their height and weight and calculated their body mass index (BMI), and their concentrations of leptin, irisin, oestradiol (E2) and testosterone (T) in the serum were detected. Results: There were significant differences in T, E2, leptin and irisin between normal weight boys and girls (P<0.05). There were statistically significant differences in T, E2 and irisin between overweight/obese boys and girls (P<0.05). Overweight/obese students had higher concentrations of irisin and leptin than normal weight students (P<0.05). The direct effect of BMI on irisin was not statistically significant in either normal weight or overweight/obese students but their indirect effects via leptin were statistically significant (for normal weight boys and girls, standardized indirect effect coefficient: 0.29 and 0.38, respectively; for overweight/obese boys and girls, standardized indirect effect coefficient: 0.36 and 0.34, respectively). There was a negative pathway of E2leptinirisin in normal weight boys (standardized indirect effect coefficient: -0.24) and a negative pathway of Tleptinirisin in overweight/obese boys (standardized indirect effect coefficient: -0.27). Conclusion: The indirect effects of BMI on irisin via leptin exists in children and adolescents of different body types. E2 was negatively correlated with leptin in normal weight boys, whereas T was negatively correlated with leptin in overweight/obese boys.